Inovasi dalam Perawatan: Evaluasi Layanan Paliatif Homecare dan Telemedicine untuk Anak Kanker di Yayasan Rachel House - Mari Esterilita; Zakiyah; Cahya, Mochamad Robby Fajar (Universitas Islam Tribakti Lirboyo Kediri, 2024)
Palliative care services have evolved to incorporate homecare and telemedicine approaches. Research indicates that palliative patients feel more comfortable receiving care at home. Telemedicine services also act as a complementary solution when palliative patients require medical assistance but face distance-related challenges. Rachel House Foundation applies both approaches in providing palliative care for cancer patients. The objective of this study is to provide an assessment of the quality of homecare and telemedicine services from the perspectives of patients’ parents or caregivers. This study employs a quantitative approach with descriptive analysis. The sample consists of 12 individuals who are parents or caregivers of the patients. The findings reveal that the quality of homecare services at Rachel House Foundation is rated as high or very satisfactory, with 100% satisfaction. Assessments by parents or caregivers regarding telemedicine services were categorized as very positive (33.33%) and fairly positive (66.67%). Based on these results, it can be concluded that palliative homecare and telemedicine services are already highly effective. However, improvements are needed in terms of 24-hour service availability, punctuality of staff, and the effectiveness of telemedicine services to match the quality of homecare services.